Głos końcowy w postępowaniu karnym - struktura tekstu = Closing speech in criminal proceedings: The structure of a text - Wiśniowski, Aleksander (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The compositional and thematic structure of a court speech is not fixed normatively. The basic structural pattern can be limited to two obligatory elements: the act of addressing the court and a lawyer`s application for a final settlement.
Keywords: przemówienie sądowe; juryslingwistyka; genologia lingwistyczna; struktura tekstu; court speech; legilinguistics; linguistic genology; text structure